New descriptions of endophalli of Timarcha Samuelson, 1819 (Coleoptera, Chrysomelidae) - Petitpierre, Eduard; Anichtchenko, Alexander (Zootaxa, 2022)
The endophalli of Timarcha arragonica Balbi, 1892, T. lusitanica (Fabricius, 1781), T. pratensis Duftschmid, 1825 and T. chloropus (Germar, 1823) are described and illustrated. The taxonomic relationships among these species and with those previously studied species are discussed.